2019
DOI: 10.1167/iovs.18-26526
|View full text |Cite
|
Sign up to set email alerts
|

Rosiglitazone Treatment Prevents Postoperative Fibrosis in a Rabbit Model of Glaucoma Filtration Surgery

Abstract: PURPOSE. To evaluate the potential antifibrotic effect of rosiglitazone (RSG), a peroxisome proliferator-activated receptor c (PPARc)-selective agonist, on subconjunctival fibrosis in a rabbit model of glaucoma filtration surgery (GFS) in vivo, and to investigate the underlying mechanisms in human Tenon's fibroblasts (HTFs) in vitro. METHODS. GFS were performed on adult male New Zealand white rabbits with chronic ocular hypertension previously established by injections of 2% methylcellulose into the anterior c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Based upon the fact that PPAR-γ belongs to the nuclear hormone receptor superfamily of ligand-activated transcription factors, and has been found to regulate fibrosis in multiple organs [ 62 , 63 ], a previous study revealed that Rosi, a synthetic PPAR-γ agonist, could moderately antagonize TGF-β-induced fibrosis by blocking the TGF-β/Smad pathway in vitro [ 61 ]. In fact, Luo et al demonstrated that Rosi can exert the anti-fibrotic activity of human tenon fibroblasts, thus suggesting that Rosi might be useful for modulating the scar formation that is frequently observed post-surgery [ 26 , 64 ]. Zhang et al recently investigated the effects and toxicities of a poly (3-hydroxybutyric acid-co-3-hydroxyvaleric acid) (PHBV)-loading Rosi membrane toward scar formation after glaucoma filtration surgery (GFS) in a rabbit model and found following results: (1) the concentration of Rosi does not affect the morphology of the RSG/PHBV membrane, and (2) the RSG/PHBV membrane effectively and safely prevents the formation of fibrosis after GFS in a rabbit model.…”
Section: Discussionmentioning
confidence: 99%
“…Based upon the fact that PPAR-γ belongs to the nuclear hormone receptor superfamily of ligand-activated transcription factors, and has been found to regulate fibrosis in multiple organs [ 62 , 63 ], a previous study revealed that Rosi, a synthetic PPAR-γ agonist, could moderately antagonize TGF-β-induced fibrosis by blocking the TGF-β/Smad pathway in vitro [ 61 ]. In fact, Luo et al demonstrated that Rosi can exert the anti-fibrotic activity of human tenon fibroblasts, thus suggesting that Rosi might be useful for modulating the scar formation that is frequently observed post-surgery [ 26 , 64 ]. Zhang et al recently investigated the effects and toxicities of a poly (3-hydroxybutyric acid-co-3-hydroxyvaleric acid) (PHBV)-loading Rosi membrane toward scar formation after glaucoma filtration surgery (GFS) in a rabbit model and found following results: (1) the concentration of Rosi does not affect the morphology of the RSG/PHBV membrane, and (2) the RSG/PHBV membrane effectively and safely prevents the formation of fibrosis after GFS in a rabbit model.…”
Section: Discussionmentioning
confidence: 99%
“…Let-7a miRNA expression has been found decreased in mouse models of liver fibrosis and in the liver and blood samples from liver fibrosis patients. Let-7a suppresses the activation of HSCs and its overexpression induces apoptosis of these cells, by interfering with the TGF-β/SMAD signaling pathway (Zhang et al, 2019). Thus, the administration of miRNAs may represent an interesting therapeutic opportunity to combat liver fibrosis.…”
Section: Organ Fibrosis Emt and Possible Anti-emt Therapeutic Stratementioning
confidence: 99%
“…It has been shown that RSG treatment prevents subconjunctival fibrosis after GFS through the inhibition of profibrotic gene expression by a mechanism that promotes autophagy in local fibroblasts. Thus, the use of RSG may represent a novel antifibrotic approach with the potential to improve the success rate of GFS (Zhang et al, 2019) (Figure 8).…”
Section: Ocular Fibrosismentioning
confidence: 99%
“…TGF-β is also an important profibrotic element, especially in fibrosis [ 34 , 35 ]. Rosglitazone, which is a PPARγ agonist, suppresses TGF-β1 expression and prevents conjunctival fibrosis after glaucoma filtration surgery [ 36 ]. In our current study, PPARγ treatment suppressed fibrotic changes in the corneal stroma, which may be induced by anti-TGF-β effects of PPARγ.…”
Section: Discussionmentioning
confidence: 99%